2004
DOI: 10.1124/mol.65.5.1092
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB Mediates Up-Regulation of Cathepsin B by Doxorubicin in Tumor Cells

Abstract: Anthracyclines such as doxorubicin remain among the most effective agents for the treatment of solid tumors and hematological malignancies. To overcome dose-limiting side effects like cardiotoxicity, an intensive effort has been undertaken to develop promising doxorubicin prodrugs that are specifically activated at the tumor site. One approach is the application of peptide prodrugs of doxorubicin. The enzyme cathepsin B catalyzes the activation of these prodrugs, and hence, the regulation of cathepsin B by ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…Besides the binding sites for Sp1, Ets and USF transcription factors, the 5′‐flanking region of the cathepsin B gene contains an NF‐κB binding site at position 1460–1471 bp of the promoter region (Figure 4A). It has been demonstrated that exposure of HeLa carcinoma cells to doxorubicin induced an NF‐κB‐dependent up‐regulation of cathepsin B (Bien et al, 2004). To assess NF‐κB activity in mtDNA‐depleted cells, we used a luciferase construct containing five copies of the DNA‐binding sequence of NF‐κB in its promoter region.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the binding sites for Sp1, Ets and USF transcription factors, the 5′‐flanking region of the cathepsin B gene contains an NF‐κB binding site at position 1460–1471 bp of the promoter region (Figure 4A). It has been demonstrated that exposure of HeLa carcinoma cells to doxorubicin induced an NF‐κB‐dependent up‐regulation of cathepsin B (Bien et al, 2004). To assess NF‐κB activity in mtDNA‐depleted cells, we used a luciferase construct containing five copies of the DNA‐binding sequence of NF‐κB in its promoter region.…”
Section: Resultsmentioning
confidence: 99%
“…However, conversely, CatB expression is believed to be NF- κ B-dependent as the promoter of CatB has NF- κ B binding site [43]. In almost all cell types, including fibroblasts, NF- κ B exists as a dimer of a p50 and p65 subunit that is retained in an inactive cytoplasmic complex by binding to the I κ B α .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, doxorubicin‐induced apoptosis involves modulation of mitochondrial structures, a process known to result in mitochondrial dysfunction, such as the leakage of cytochrome c and the opening of mitochondrial permeability transition pores 5, 12. Lysosomal proteins are also targets of doxorubicin and the drug can modify lysosomal morphology and enzyme activity 13, 14. Recently, transcriptional analysis of doxorubicin‐induced cytotoxicity was performed to gain a more global view of the effects of the drug in HepG2 cells 15.…”
Section: Introductionmentioning
confidence: 99%